Ethnobotanical, Phytochemical and Pharmacological Profile of Boerhaavia diffusa Linn. - A Review - A. Bhalerao, Satish (Asian Journal of Chemistry, 2012)
Boerhaavia diffusa, commonly known as Punarnava in Sanskrit, is a herbaceous plant and a member of Nyctaginaceae family. It is widely distributed in tropics and sub tropics. It has a long history of uses by indigenous and tribal people and in Ayurvedic medicines. In the traditional system of medicines, Boerhaavia diffusa roots have been widely used for the treatment of dyspepsia, jaundice, enlargement of spleen and abdominal pain. It is also used as antistress agent. Root extract had antihepatotoxic properties. Plant is also used as blood purifier, laxative, expectorant, diuretic. Boerhaavia diffusa contains a large number of bioactive chemical compounds such as flavonoids, alkaloids, steroids, triterpenoids, lipids, lignins, carbohydrates, proteins and glyco-proteins. Many rotanoids have been isolated from root of this plant. These include a series of boeravinones. Punernavoside, a phenolic glycoside is reportedly present in root. Pharmacological activities of the plant include antibacterial, antidiabetic, hepatoprotective, antiastrogenic, antoinflametory, anticonvulsant, antistress and adaptogenic activity, immunomodulatory, diuretic, antifertility, antioxidant, antiviral, antifibrinolytic. Multiple benefits of Boerhaavia diffusa made it a true miracle of nature. Plants contain thousands of constituents and are valuable sources of new and biologically active molecules. In spite of tremendous potential, this plant has not yet developed as a drug by pharmaceutical industries. The objective of this review is to show the recent advances in the exploration of plant Boerhaavia diffusa as phytotherapy and to illustrate its potential as a therapeutic agent.